KEEFEKTIFAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN TIPE STAD TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA MTs - Nuralam; Noera Khalidah (Jurnal Numeracy, 2019)
Mathematical problem solving skills of students are still low because of lack of student involvement in the learning process. One alternative to improve this is by teaching the students the problem-based learning models with of the STAD type. This study aimed to describe teacher activity, student activity, student response, and improvement of students' problem solving skills learned through the problem-based learning model with the STAD type. This study used classroom action research with the subjects included the students in class VIIIB MTsN 1 Pidie. Data were collected by observation, tests and response questionnaire. The data were than analyzed by using quantitative descriptive statistics. The results of the study showed that the teacher activity had an average 83% or in the good category, the students’ activities during learning were in the active category, the students’ responses had an average of 2.92 or in the positive category, and students’ problem solving skills had increased. Therefore, it can be concluded that the problem-based learning model with the STAD type was effective and successful in improving the students’ mathematical problem solving skills. Abstrak Kemampuan pemecahan masalah matematika siswa masih rendah karena kurang keterlibatan mereka dalam proses pembelajaran. Salah satu alternatif agar keefektifan ditingkatkan melalui model pembelajaran berbasis masalah dengan tipe STAD. Penelitian ini bertujuan untuk mendeskripsikan aktivitas guru, aktivitas siswa, respon siswa dan peningkatan kemampuan pemecahan masalah siswa yang dibelajarkan melalui model pembelajaran berbasis masalah dengan tipe STAD. Penelitian ini menggunakan tindakan kelas dengan subjek yang diteliti kelas VIIIB MTsN 1 Pidie. Pengumpuan data melalui observasi, tes dan angket respon. Data dianalisis menggunakan statistik deskriptif. Hasil penelitian diperoleh setelah membelajarkan dengan model pembelajaran berbasis masalah dengan tipe STAD bahwa aktivitas guru rerata sebesar 83% dalam kategori baik, aktivitas siswa selama pembelajaran dalam kategori aktif, respon siswa rerata sebesar 2,92 dalam kategori positif, dan kemampuan pemecahan masalah siswa meningkat. Oleh karena itu disimpulkan bahwa model pembelajaran berbasis masalah dengan tipe STAD efektif secara proses dan hasil dalam meningkatkan kemampuan pemecahan masalah matematika siswa. Kata kunci: Kemampuan matematika, kemampuan pemecahan masalah, model pembelajaran, model pembelajaran berbasis masalah dengan tipe STAD